Diffusion-weighted imaging is helpful in the accurate non-invasive diagnosis of breast abscess: correlation with necrotic breast cancer. (22nd March 2018) - Wang, Cuiyan; Eghtedari, Mohammad; Yang, Wei Tse; Dogan, Basak Erguvan
Abstract : Clinical differentiation of atypical breast abscesses from necrotic tumour in premenopausal women is challenging and may delay appropriate therapy. In this case report, we present a 36-year-old woman with signs, symptoms and conventional imaging features of malignancy who underwent breast MRI. On diffusion-weighted imaging (DWI), profoundly low apparent diffusion coefficient values were a distinguishing sign of breast abscess from necrotic breast cancer, and helped manage the patient conservatively. We present a companion case of necrotic breast tumour highlighting significant differences in DWI.